To promote Pekan Nabalu as one of the tourism attraction in Malaysia by redesigning corporate / Sweney Simbeh - Sweney Simbeh (Faculty of Art and Design, 2013)
This section is an overview of background research based on literature review. Chapter one is about the Pekan Nabalu. From this academic writing, I have study about the Pekan Nabalu view besides to get solution for this research. Chapter two is about research and methodology. In this chapter ,1 want to propose my research objectives. Research objective are important to us to know the objective by doing this research. This chapter also including different kind of research to get information on this project. Research methodology focus on what type of method that we using that suitable for our issues. It is also help us to get more data and also evidence for the issues. This is the way to getting more detail about this place. Chapter three is analysis and finding. In this chapter I’m using the method of interview, and questionnaire to gain information. This section provide the discussion based on the original data obtained from the research method.lnterview review that I’m doing is to get know about Pekan Nabalu with interviewing with face to face. It is a useful to obtain detail with knowing the information, perception and opinion. Questionnaire used to get back the respond others to this research. After finished distributes a questionnaire, I made analysis to get a result from questionnaire. Finding have to be made to know the result from the data analysis. The final is describe the conclusion and recommendation. This section describe the conclusion for research that I’ve done. This is also explain the recommendation which is the way that should be doing to obtain the purpose of this research. This is describe with objective and the development of practical recommendations based on relevant research.